2019
DOI: 10.1002/anie.201901161
|View full text |Cite
|
Sign up to set email alerts
|

Selenium‐Modified Microgels as Bio‐Inspired Oxidation Catalysts

Abstract: Active colloidal catalysts inspired by glutathione peroxidase (GPx) were synthesized by integration of catalytically active selenium (Se) moieties into aqueous microgels.A diselenide crosslinker (Se X-linker) was successfully synthesized and incorporated into microgels through precipitation polymerization, along with the conventional crosslinker N,N'methylenebis(acrylamide) (BIS). Diselenide bonds within the microgels were cleaved through oxidation by H 2 O 2 and converted to seleninic acid whilst maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 61 publications
(66 reference statements)
2
46
0
Order By: Relevance
“…Beside these studies, there were sporadic reports on the redox chemistry of selenium, such as reversibletuning Krafft temperature and the reversible sol-gel transition. 179,180…”
Section: Multiresponsive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside these studies, there were sporadic reports on the redox chemistry of selenium, such as reversibletuning Krafft temperature and the reversible sol-gel transition. 179,180…”
Section: Multiresponsive Materialsmentioning
confidence: 99%
“…217,218 In general, transition metals are broadly studied, because these heterogeneous catalysts are easy to process and separate after the reactions. 219 However, selenium-based catalysts have also been given much attention, including organoselenium compounds, polymer-loaded selenium agents and selenium-containing polymers, due to their better catalytic activity and selectivity. In the past few years, some studies involving organoselenium compounds as catalysts have been reported.…”
Section: Application As Catalystsmentioning
confidence: 99%
“…By choosing and rationally designing the monomers, the prepared microgels can physically or chemically be responsive to external stimuli, for example pH, [ 4,5 ] icon strength, [ 6 ] light, [ 7 ] and pressure. [ 8 ] Considering the physical and chemical property can be tailored as needed, microgels have been widely utilized in many fields including drug delivery, [ 9 ] catalysis, [ 10 ] metal detection, [ 11 ] and biosensors. [ 12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the last time many catalytic hydrogel systems have been reported, emphasizing the potentially broad applicability of this system , , . Despite probably being as well exciting, we did not investigate the catalyst recyclability in this study, as we were rather interested in a process delivering constant product quality.…”
Section: Introductionmentioning
confidence: 99%